2000
DOI: 10.1016/s0735-1097(00)00635-5
|View full text |Cite
|
Sign up to set email alerts
|

Prospective randomized comparison of antiarrhythmic therapy versus first-line radiofrequency ablation in patients with atrial flutter

Abstract: In a selected group of patients with atrial flutter, RF ablation could be considered a first-line therapy due to the better success rate and impact on quality of life, the lower occurrence of atrial fibrillation and the lower need for rehospitalization at follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
199
2
6

Year Published

2002
2002
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 351 publications
(216 citation statements)
references
References 22 publications
6
199
2
6
Order By: Relevance
“…Natale et al 32 have suggested catheter ablation as the first-line therapy in patients with AFl and normal or mildly enlarged left atrial size. They found a higher success rate, better quality of life, lower occurrence of AF, and less need for rehospitalization at follow-up when compared with drug treatment.…”
Section: Resultsmentioning
confidence: 99%
“…Natale et al 32 have suggested catheter ablation as the first-line therapy in patients with AFl and normal or mildly enlarged left atrial size. They found a higher success rate, better quality of life, lower occurrence of AF, and less need for rehospitalization at follow-up when compared with drug treatment.…”
Section: Resultsmentioning
confidence: 99%
“…This is based on decades of experience demonstrating the safety and efficacy of catheter ablation of AFL as well as data from clinical trials comparing ablation with AAD therapy. 230,504,511,1397 The writing group recommends that if a patient has a history of typical AFL or typical AFL is induced at the time of AF ablation, delivery of a cavotricuspid isthmus linear lesion is recommended (Class I, LOE B-R, Table 3). …”
Section: Section 5: Strategies Techniques and Endpointsmentioning
confidence: 99%
“…[3][4][5][6] Despite a high success rate, ablation of the CTI can be extremely difficult in some patients. 7,8 The vast span seen in ablations (1 to 30 or more RF applications) must thus reflect phenomena as yet unqualified.…”
mentioning
confidence: 99%